Janitschek on the right. The general secretary of the S.I. with the international secretary of the Democratic Action Party of Malaysia - Klaus, Heinz (1976)
Janitschek on the right. The general secretary of the S.I. with the international secretary of the Democratic Action Party of Malaysia.